Mitotic regulation of the human anaphase-promoting complex by phosphorylation - Kraft, Claudine (Oxford University Press, 2003)
The anaphase-promoting complex (APC) or cyclosome is a ubiquitin ligase that initiates anaphase and mitotic exit. APC activation is thought to depend on APC phosphorylation and Cdc20 binding. We have identified 43 phospho-sites on APC of which at least 34 are mitosis specific. Of these, 32 sites are clustered in parts of Apc1 and the tetratricopeptide repeat (TPR) subunits Cdc27, Cdc16, Cdc23 and Apc7. In vitro, at least 15 of the mitotic phospho-sites can be generated by cyclin-dependent kinase 1 (Cdk1), and 3 by Polo-like kinase 1 (Plk1). APC phosphorylation by Cdk1, but not by Plk1, is sufficient for increased Cdc20 binding and APC activation. Immunofluorescence microscopy using phospho-antibodies indicates that APC phosphorylation is initiated in prophase during nuclear uptake of cyclin B1. In prometaphase phospho-APC accumulates on centrosomes where cyclin B ubiquitination is initiated, appears throughout the cytosol and disappears during mitotic exit. Plk1 depletion neither prevents APC phosphorylation nor cyclin A destruction in vivo. These observations imply that APC activation is initiated by Cdk1 already in the nuclei of late prophase cells.